446 Bronchial Asthma among University Students, Ajman, Uae. (October 2012) - John, LJ; Arifulla, M; Sreedharan, J
Abstract : Background and Aims: Prevalence of wheezing and allergies among the Arab countries are on a rise due to urbanization resulting in substantial environmental changes. Prevalence of wheezing is about 14% among school children but data on adolescents in the Gulf region is lacking. This study aimed to assess the prevalence of wheezing and bronchial asthma among undergraduate students of Gulf Medical University. Methods: Cross-sectional study was conducted among undergraduate students of Gulf Medical University using a self administered questionnaire as research instrument for data collection. The demographic data and the wheezing and bronchial asthma characteristics, family history was collected and analyzed using SPSS version 19. Chi square test used to test association between variables. Results: A total of 255 students were included; of which 71(27.8%) had wheezing (Females were 66% and males 34%); Wheezing was more prevalent among African(18%) and Pakistani(16%) nationals. Of 71 students, 41(57.7%) students experienced 1–3 episodes in last one year, 13(18.3%) had episodes limiting their speech. Exercise induced wheezing was experienced by 62 (24.3%) participants. The wheezing episodes were most frequent in January and March (p<0.05). Positive family history of wheezing was reported by 29(40.8%) students. 40.8% students reported that wheezing interfered with their daily and extra-curricular activities. Of the total, 31(12.2%) students gave history of bronchial asthma of which 16 (50%) had a positive family history of bronchial asthma. Conclusions: Overall higher proportion of students had wheezing symptoms especially among the African students. Strong family history was also noted both wheezing and bronchial asthma.